Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1756-8722-6-27
|View full text |Cite
|
Sign up to set email alerts
|

MEK and the inhibitors: from bench to bedside

Abstract: Four distinct MAP kinase signaling pathways involving 7 MEK enzymes have been identified. MEK1 and MEK2 are the prototype members of MEK family proteins. Several MEK inhibitors are in clinical trials. Trametinib is being evaluated by FDA for the treatment of metastatic melanoma with BRAF V600 mutation. Selumetinib has been studied in combination with docetaxel in phase II randomized trial in previously treated patients with advanced lung cancer. Selumetinib group had better response rate and progression-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(176 citation statements)
references
References 111 publications
7
162
0
1
Order By: Relevance
“…We studied the novel MEK inhibitor GDC-0623, which has been shown to have superior efficacy against KRAS compared with BRAF mutant tumors (10). We found that GDC-0623 treatment can potently up-regulate BIM and to a greater extent than observed for other MEK inhibitors that have undergone clinical evaluation (32,33). ERK silencing in GDC-0623-treated cells was shown to enhance BIM induction.…”
Section: Discussionmentioning
confidence: 98%
“…We studied the novel MEK inhibitor GDC-0623, which has been shown to have superior efficacy against KRAS compared with BRAF mutant tumors (10). We found that GDC-0623 treatment can potently up-regulate BIM and to a greater extent than observed for other MEK inhibitors that have undergone clinical evaluation (32,33). ERK silencing in GDC-0623-treated cells was shown to enhance BIM induction.…”
Section: Discussionmentioning
confidence: 98%
“…5 CI-1040 was the first to enter clinical trials in 2000. 2,6 Since that time, at least 13 different MEK inhibitors have been developed and evaluated in clinical trials. Recent clinical trials have used MEK inhibitors alone and in combination with other chemotherapeutic agents to treat a variety of cancers including melanoma, ovarian cancer, leukemia, lymphoma, thyroid cancer, colorectal cancer, non-small cell lung cancer, biliary cancer, and pancreatic cancer and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ERK is phosphorylated by MEK proteins (also known as MAPK2K proteins) and the phosphorylation is abrogated with MEK inhibitors (Akinleye et al, 2013). We chose the widely used MEK inhibitor PD98059 to investigate the effect of abrogation of ERK phosphorylation on cell proliferation in the presence or absence of Drp1.…”
Section: The Mtcyce Pool Is Modulated By Mitochondrial Bioenergetics mentioning
confidence: 99%